Mental health services for the mobile population: Limitations of the public, private, and civil society sectors in Mexico - Saavedra, Nayelhi (2024)
The strategies implemented by the State to provide mental health services to the mobile population have been weak and discontinuous. One of the reasons is the reduced budget assigned to infrastructure and human resources in the public health sector. So far, the task has fallen directly to civil society organizations (CSO), associations and international agencies (IA), and indirectly to financiers. However, because of limitations and dynamics of all of them, the services they offer fail to satisfy the care needs of migrants. The aim of the study is to know who offer mental health services, how do they offer it, and to understand the factors which are underneath that restrict supply of services. This is a descriptive exploratory research. We use a qualitative methodology. From 2019 to 2023, we conducted 81 interviews with members of CSO, associations, IA and personnel from government agencies, in places where important flows of migrants converge: CDMX, Tijuana, and towns in three states, Morelos, Hidalgo and Michoacán. We realized that the obstacles identified by the participants are related to public policies and financing, the human resources available in CSO, and the material, administrative and human resources in the public sector. The issue underlying the limitations is the lack of explicit regulations and the hidden norms that shape any actions of public sector staff, CSO and IA, as well as funders.